TRANSFORMATIONAL LEADERSHIP INFLUENCE AND CORPORATE CULTURE ON PERFORMANCE (PERCEPTIONAL STUDY OF BJB SYARIAH BANK EMPLOYEES IN SUMEDANG SUB-BRANCH OFFICE) - Eggi Indriani Pratami (Universitas Kuningan, 2020)
BJB Syariah Bank is ranked sixth out of all Syariah Banks in Indonesia. To get good performance, BJB Syariah Bank KCP Sumedang, requires high quality of human resources, because humans are the most important asset for achieving the goals of the company. Companies must be able to develop their employees to become quality employees and can improve their performance for the development of the company. The research method uses quantitative methods. In this research, the writer uses the descriptive method. Furthermore, the data collection techniques obtained from primary data and secondary data, primary data sources were obtained through interviews, observations and questionnaires distributed to 13 respondents who are employees of BJB Syariah Bank Sub-Branch Office of Sumedang. While the secondary data obtained from literature, books, journals and other sources. Then arranged systematically and analyzed according to the existing theories, so it can be formulated for the steps to test the truth of the proposed hypothesis. Statistical calculations on transformational leadership variables, company culture and employee performance using multiple regression obtained beta coefficients of transformational leadership on performance at 0.637, corporate culture on performance at 0.157. The results of the simultaneous influence of transformational leadership and company culture on employee performance is 0.535, which means that the coefficient of determination is 53.50%, it means that the employees’ performance is influenced by transformational leadership factors and company culture by 53.50% and the rest is influenced by other factors. From the description above, it can be concluded that the hypothesis proposed by the writer can be accepted.